The roles and applications of neural stem cells in spinal cord injury repair - Guo, Wen; Zhang, Xindan; Zhai, Jiliang; Xue, Jiajia (Frontiers in Bioengineering and Biotechnology, 2022)
Spinal cord injury (SCI), which has no current cure, places a severe burden on patients. Stem cell-based therapies are considered promising in attempts to repair injured spinal cords; such options include neural stem cells (NSCs). NSCs are multipotent stem cells that differentiate into neuronal and neuroglial lineages. This feature makes NSCs suitable candidates for regenerating injured spinal cords. Many studies have revealed the therapeutic potential of NSCs. In this review, we discuss from an integrated view how NSCs can help SCI repair. We will discuss the sources and therapeutic potential of NSCs, as well as representative pre-clinical studies and clinical trials of NSC-based therapies for SCI repair.